Combating Disasters in Oil and Gas Well Drilling (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
This article explores the key strategies and technologies used to combat disasters in oil and gas well drilling. These disasters can include blowouts, equipment failure, and environmental hazards. Innovations in real-time monitoring, advanced blowout preventers, and improved safety protocols are discussed in detail. This paper aims to provide insights into current best practices and future directions for improving safety in oil and gas extraction.